Cancer Stem Cells as a new promising approach of efficient oncological treatment - the review of literature - Szumna, Klaudia Daria; Piędel, Faustyna; Jasielski, Patryk; Grosman, Sylwia; Habaj, Kamila; Filip, Agata (Journal of Education, Health and Sport, 2020)
Introduction and purpose: For many years a lot of research projects have been conducted with the aim to discover special cells, which are responsible for a neoplasm development. One of the theories concerns cancer stem cells (CSCs). This theory presumes the existence of original, undifferentiated cancer cells. These cells are capable of transform to all types of cells in neoplasm mass. The purpose of this study was to review the currently available data about the theory of CSCs and especially potential usage of this theory in oncological treatment. Pubmed and Scopus databases from the last 10 years were searched for phrase “cancer stem cells”. A brief description of the state of knowledge: Impaired signalling pathways lead to an occurrence of CSCs which may contribute to the development of neoplasm eventually. It is proved, that gamma secretase inhibitors impede Notch signalling pathway, which leads to a decrease of tumour markers expression and consequently decline in vivo tumour growth. It is believed that epigenetic mechanisms, including DNA methylation, histones alteration and RNA orientation are pivotal regulators of CSCs. It was shown, that histone deacetylases (HDAC) modulate refractoriness on chemotherapy in haematological tumours. It is also evidenced that peculiar designed microRNA directly inhibit CD44 which suppresses prostatic cancer stem cells and its metastases. CSCs have high expression of programmed death-ligand 1 (PD-L1) including breast and colon cancer, which proclaims in favour of immunotherapy aimed on CSCs. Conclusions: Constantly growing knowledge about CSCs biology is creating new opportunities of detection, isolation and design of the therapies aimed on CSCs.